Grapevine virus L: a novel vitivirus in grapevine - Debat, Humberto Julio (2019)
Vitiviruses are ssRNA(+) viruses in the family Betaflexiviridae (subfamily Trivirinae). There are currently 10 ICTV recognized virus species in the genus; nevertheless, the extended use of NGS technologies is rapidly expanding their diversity and official recognition of six more have been proposed recently. Here, we present the characterization of a novel virus from grapevine, which fits the genomic architecture and evolutionary constraints to be classified within the Vitivirus genus. The detected virus sequence is 7607 nt long, including a typical genome organization of ORFs encoding a replicase (RP), a 22 kDa protein, a movement protein, a coat protein (CP) and a nucleic acid binding protein. Phylogenetic analyses based on the predicted RP and CP proteins unequivocally place the new virus within the Vitivirus genus. Multiple independent RNAseq data confirmed the presence of the detected virus in berries at diverse developmental stages. Additionally, we detected, confirmed, and assembled virus sequences from grapevine samples of distinct cultivars from America, Europe, Asia and Oceania, sharing 74.4%–97.8% nt identity, suggesting that the identified virus is widely distributed and diverse. We propose the name grapevine virus L (GVL) to the detected Vitivirus.